P-174 Morphokinetic criteria for embryo selection might be dependent on culture conditions. (30th June 2022) - Valera, M.Á; Albert, C; Galán, A; Insua, M.F; De los Santos, M.J; Meseguer, M
Abstract: Study question: Does embryo culture in a high humidity content atmosphere affect the potential of morphokinetics as a biomarker for implantation? Summary answer: Culturing embryos in a high relative humidity atmosphere modify the predictive value of morphokinetic parameters. What is known already: Culturing embryos in a high humidity atmosphere has been proposed not only as a more physiological approach, closer to the in-vivo environment of the embryos, but also as a culture strategy that may improve clinical outcome, especially in treatments with compromised embryo quality. On the other hand, the role of morphokinetics (MK) as a biomarker of embryo viability and implantation potential has been widely recognized and it has increasingly been implemented in IVF laboratories as a selection method. However, it has not been studied how a humid culture strategy might impact the selective capacity of morphokinetics. Study design, size, duration: This was a retrospective study, performed over 386 transferred embryos, cultured until blastocyst in a Geri time-lapse system (Genea Biomedx, Australia), either in a dry (n = 199) or humidified chamber (n = 187). Embryos belong to 363 ICSI treatments, including both autologous and ovum donation cycles, performed in a single IVF clinic during 3 consecutive years. Participants/materials, setting, methods: Embryo cohorts were randomly assigned to dry (DC, n = 187) or humid culture (HC, n = 175) in a Geri incubator, using single-step Gems culture medium (Genea Biomedx, Australia). MK parameters were automatically annotated by the Geri Assess 2.0 software. 1 or 2 embryos were selected for fresh transfer according to morphological and morphokinetic criteria. MK parameters were compared by ANOVA test between embryos that achieved implantation (KID+) and did not (KID-) and between the study groups. Main results and the role of chance: Overall, KID+ embryos (n = 221) had significantly ( P < 0.05) lower timings in several MK parameters than KID- embryos: time of pronuclei fading (tPNf: 22.40±2.26h vs 23.16±2.60h), time of cleavage to 2 cell stage (t2: 24.99±2.59h vs 25.72±2.79h), 5 cells (t5: 48.01±5.23h vs 49.18±5.73h) and 6 cells (t6: 50.79±4.57h vs 52.10±6.03h). Those parameters were not significantly different between embryos from DC and HC: tPNf=22.85±2.38h (DC) vs 22.60±2.51h (HC), P =0.342; t2= 25.54±2.55h (DC) vs 25.05±2.82h (HC), P =0.072; t5= 48.79±5.23h (DC) vs 48.21±5.72h (HC), P =0.303; t6= 51.56±5.20h (DC) vs 51.13±5.37h (HC), P =0.443. Later events, although occurred sooner in embryos cultured in humid conditions were not related to the implantation outcome. When stratifying the results by the two culture conditions, the MK parameters that differentiate embryos that achieved or not implantation were different in each group. MK parameters in DC: tPNf =22.59±2.31h KID+vs 23.19±2.43h KID-, P =0.084; t2 = 25.27±2.45h KID+ vs 25.91±2.65h KID-, P =0.080; t5 = 48.12±5.05h KID+ vs 49.69±5.36h KID-, P =0.038; t6 = 50.82±4.53h KID+ vs 52.54±5.85h KID-, P =0.026. MK parameters in HC: tPNf =22.19±2.20h KID+vs 23.12±2.78h KID-, P =0.014; t2 = 24.69±2.71h KID+ vs 25.52±2.92h KID-, P =0.046; t5 = 47.89±5.44h KID+ vs 48.64±6.08h KID-, P =0.384; t6 = 50.77±4.64h KID+ vs 51.62±6.23h KID-, P =0.307. Limitations, reasons for caution: Although patient demographics were similar in both study groups, a degree of heterogeneity in the population is possible because of the retrospective nature of the analysis. Other variables such as the morphology of the embryo should be considered for a more in-depth analysis. Wider implications of the findings: Culture in high relative humidity conditions seems to influence the morphokinetics of embryo development. The application of a selection system that include morphokinetic parameters for choosing the embryo with the highest implantation potential should be adapted to the specific culture conditions in use. Trial registration number: Not applicable